Hematopoietic stem cell transplantation in CD40 ligand deficiency: A single-center experience - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (WILEY, 2020)
Deficiency of the CD40L, expressed on the surface of T lymphocytes, is caused by mutations in the glycoproteinCD40L (CD154)gene. Resulting defective humoral and cellular responses cause a clinical presentation that includes recurrent sinopulmonary bacterial infections, opportunistic infections, sclerosing cholangitis, neutropenia, and autoimmune manifestations. HSCT represents the only curative treatment modality. However, the therapeutic decision to use HSCT proves challenging in many cases, mainly due to the lack of a phenotype-genotype correlation. We retrospectively reviewed patients with CD40L deficiency who were transplanted in Antalya and Goztepe MedicalPark Pediatric HSCT units from 2014 to 2019 and followed by Akdeniz University School of Medicine Department of Pediatric Immunology. The records of eight male cases, including one set of twins, were evaluated retrospectively. As two transplants each were performed on the twins, a total of ten transplants were evaluated. Conditioning regimens were predominantly based on myeloablative protocols, except for the twins, who received a non-myeloablative regimen for their first transplantation. Median neutrophil and platelet engraftment days were 13 (range 10-19) and 14 (range 10-42) days, respectively. In seven of ten transplants, a CMV reactivation was developed without morbidity. None of the patients developed GVHD, except for one mild case of acute GVHD. All patients survived, and the median follow-up was 852 days. Our data show that HSCT for patients with CD40 ligand deficiency is a potentially effective treatment for long-term disease control.
Keywords: CD40L deficiency; children; hematopoietic stem cell transplantation; HYPER-IGM SYNDROME